Pressurized Liquid Extraction (PLE) as an Innovative Green Technology for the Effective Enrichment of Galician Algae Extracts with High Quality Fatty Acids and Antimicrobial and Antioxidant Properties - Paz Otero; Somaris E. Quintana; Guillermo Reglero; Tiziana Fornari; Mónica R. García-Risco (Marine Drugs, 2018)
Marine organisms are potentially prolific sources of high qualify fatty acids that represent useful leads in the development of new nutraceutical agents. In this work, we investigated the lipid composition of six algae species from the Northwest of Spain (Ulva intestinalis, Ulva lactuca, Fucus vesiculosus, Dictyota dichotoma, Cystoseira baccata and Himanthalia elongata) and compared the antioxidant and antibacterial activity of ethanolic extracts obtained by pressurized liquid extraction (PLE). Furthermore, Fucus vesiculosus (F. vesiculosus) PLE using five solvents of different polarities (hexane, ethyl acetate, acetone, ethanol and ethanol:water 50:50) at three temperatures (80 °C, 120 °C and 160 °C) was investigated. F. vesiculosus ethanolic PLE extract presents considerably higher capacity of inhibiting 50% of DPPH (1,1-diphenyl-2-picryl hydrazyl) (IC50 = 7.17 μg/mL) in comparison with the rest of macroalgae studied. Moreover, the potential antimicrobial activity tested on E. coli and S. aureus shows that F. vesiculosus extract produced the best inhibition (IC50 was 2.24 mg/mL (E. coli) and 1.27 mg/mL (S. aureus)). Furthermore, regarding the different solvents and temperatures used to investigate F. vesiculosus PLE, results showed that this technique using ethyl acetate is a selective method to enrich long chain fatty acids (oleic acid, arachidonic acid and eicosapentaenoic acid) with ω-6/ω-3 ratios close to 2.7.